Gaucher′s disease with uncommon presentations - Gupta Sanjay; Mondal Palash; Basu Nandita; Mallick Mamata (Journal of Cytology, 2009)
Gaucher′s disease is the most common lysosomal storage disorder gene defect, which leads to deficiency or decreased activity of glucocerebrosidase, followed by accumulation of glucosylceramide. There is autosomal recessive transmission leading to varied clinical manifestations. This disease has three main types: Type I - nonneuronopathic; type II - acute neuronopathic; and type III - chronic neuronopathic. The nonneuronopathic type has the highest prevalence and also the greatest variability. The authors here report two cases of Gaucher′s disease with uncommon presentations in early childhood, highlighting the importance of early diagnosis of the disease, as now-a-days enzyme replacement therapy may arrest further progress of disease.